EIB Working Paper 2020/09 - Investment vs debt trade-offs in the post-COVID-19 European economy - Pál, Rozália (European Investment Bank, 2020)
This paper estimates the revenues lost by European firms during the COVID-19 crisis, taking into account different scenarios regarding policy support and the length of the crisis. It examines the likely effect of such revenue losses on firms' internal financing capacity and on investment, suggesting that the COVID-19 crisis may trigger an fall in corporate investment greater that that experienced during the Great Financial Crisis, with firms facing a trade-off between reduced investment and greater indebtedness. A macro-model based on historical data also suggests that the decline in corporate investment would likely be within the computed ranges, should the estimated gap in firm revenues materialise as the result of the crisis.